Питание и анализ некоторых элементов баланса энергии у черноморских крабов - (:unkn) unknown (My University, 1970)
Показано, что величина среднесуточных рационов у каменного краба, травяного, мраморного и водолюба находится в степенной зависимости от веса тела. Хотя в связи с линькой весовой рост у крабов носит прерывистый характер, накопление энергетических резервов в тканях идет постоянно. Такой своеобразный «скрытый» рост сопровождается определенными изменениями в соотношении сухого и сырого веса, калорийности на 1 г сырого веса животных. Величина усвояемости для рассмотренных видов крабов довольно высока: 92,9-98,7%. Коэффициент использования энергии ассимилированной пищи на рост (К2) без учета затрат на образование яиц составляет 20-29%, с учетом их — 32-47%.
Nutrition and Analysis of Some Elements of Energy Ваlance in the Black Sea Crabs
The magnitude of average day rations in E. spinifrons, C. maenas, P. marmoratus and X. hydrophilus is shown to be in power dependence on body weight. Although the weight growth in crabs in connection with moult is of an interrupted character, the accumulation of energetic reserves in tissues proceeds constantly. Such a peculiar «latent» growth is accompanied by definite changes in the ratio of dry and fresh weight caloricity per 1 g of fresh weight of animals. The value of assimilating ability for the considered species of crabs is rather high: 92.9-98.7%. The coefficient of utilization of assimilated food energy for growth (K2) without taking into account the expenditures for egg formation amounts to 20-29%, with regard for the expenditures — 32-47%.